Reciprocals among Political Utopianism Political Myths and Political Reality Evidences from Sri Lanka - Purasinghe, P.L.T. (Cabell’s Directories of Publishing, 2017)
There is an unbreakable and a powerful relationship between politics and utopianism. Politics is a continuous struggle for power. Therefore it is a continuous struggle occurred openly at a time as well as closely at another time among opposite parties to occupy power in practical fields established the power and spread lit. There is an apparentcontradiction between the power struggle practically in the society and conceptual politics. Conceptual politics indicate a nature of utopianismod ideal and the struggle for power exercised practically in the society is a very complicated process moving between reality and myths, reasonability and unreason ability, justice and in justice, morality and immorality, non-violence and violence, practical politics can happen through bullet or ballet. There for according to the nature of success in the above mentioned process, the final results of the political struggle are determined. Here a wide distance between conceptual politics and practical politics can be identified. This contradiction is that political conceptions do not become the reality. This paper critically examines the number of political myths and their impact to the political system of Sri Lanka.
Keywords: utopianism, political myths, political system, Sri Lanka